Carcass characteristics of male Desert goats in Elobeid area in North Kordofan State, Sudan - Elimam, Mohmed E.; Ombabi, Yassir A. (Gezira Journal of Agricultural Science; Vol 5 No 2 (2007), 2007)
Body components and carcass characteristics of the Desert goat, which is an important meat breed in the Sudan, were studied in Elobeid area in North Kordofan State in November 2005. Six males at < 1 and 1 year old (3 in each group) were bought from Elobeid livestock market and slaughtered according to Islamic rituals. There were significant differe-nces (P < 0.05) in weights of blood, leg, heart, mesenteric fat and testicles and no significant differences in the percentages of body components on empty body weight basis between the two age groups. Slaughter weight, empty body weight and hot carcass weights were increased significantly (P < 0.05) with increasing slaughter age and were heavier at 1 year old. Dressing percentages on live body weight and empty body weight basis were higher at 1 year old with no significant differences between the two age groups and the empty body weights were higher compared to the live body weight. The percentages of total carcass muscles and fat were increased and that of bones were decreased with increasing age. There were no significant differences between the two age groups in ratio of muscle to bone, muscle to fat and whole sale cuts. There were significant (P < 0.05) differences between the two age groups in carcass moisture, protein, fat and ash. Longissmus dorsi area was highly significantly (P < 0.01) increased with increasing slaughter age.